The Relevance of Ibn Tufail's Economic Theory to Modern Economic Thought: A Critical Analysis of the Concept of Rationality and Its Implications for Islamic Economic Development - Muhammad Widinur Caronge; Siradjuddin; Idris Parakkasi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The purpose of this study is to analyze the relevance of Ibn Tufail's theory of rationality in Hayy ibn Yaqzan to modern economic thought and its implications for Islamic economic development. This study uses a qualitative method based on a philosophical literature review. This study highlights two main aspects the epistemology of rationality, which emphasizes the independence of reason and empirical experience, and the spiritual ethics of economics, which balances the material and moral dimensions. The results of the study indicate that Ibn Tufail's rationality differs from the purely utility oriented homo economicus. Ibn Tufail offers an integrative rationality that unites reason, ethics, and spirituality, positioning humans as socially and divinely responsible caliphs. The implications of this study can be the basis for formulating Islamic economic policies that are just, sustainable, and oriented towards maqasid al-shariah. This study also recommends further research to develop a model of Islamic rationality in public policy and contemporary economic practice.